Internal marketing as a tool to achieve the organizational commitment of the nursing professional, Huánuco - 2018 - Maximiliano-Fretel, Katherine M. (2019)
The purpose of the study was to know the influence of the use of Internal Marketing as a tool in the organizational commitment of the nursing professional. The level of research was explanatory, prospective, observational, cross-sectional and analytical. The sample population consisted of 78 nursing professionals. The technique used was the survey and as instruments, two questionnaires: organizational commitment and internal marketing; those that were applied after signing the informed consent for the elements of study. It was determined that, 46.2% who report that Internal Marketing is used in the health establishment, evidence a healthy organizational commitment; while 35.9% showed an unhealthy organizational commitment because they say that Internal Marketing is not used in the hospital. Considering that the study variable is nominal and ordinal, the Chi2 test statistic is used, with 1 degree of freedom and 5% of error alpha. The calculated Chi2 was 31,671, p value 0.000 (<0.05). In conclusion, the general hypothesis of research is accepted: The use of Internal Marketing significantly influences as a tool in the organizational commitment of the nursing professional of the Regional Contingency Hospital Hermilio Valdizán Medrano, Huánuco - 2018.